Effects of team-teaching on senior school students’ achievement in adaptation in Ilorin, Nigeria - Mulkah Adebisi Ahmed; Ganiyu Bello; Hafsat I. Alabi; Musa M. Sulaiman; Aduke R. Ahmed (Universitas Ahmad Dahlan, 2022)
This study analyzed the effects of Team Teaching on Senior School Students’ Achievement in Adaptation. A 20-item multiple-choice question entitled Adaptation Achievement Test (AAT) was validated and distributed to 99 students that participated in the study. The equivalent of the groups was determined before the commencement of the study through pretest administration. A quasi-experimental design was adopted, hypotheses one and two were tested using paired sample t-test, while three were tested using ANCOVA. The result showed no statistically significant difference in students' achievement in adaptation when exposed to team teaching. The study also discovered a non-statistically significant difference in the achievement of males and females; and in the achievement of the low, medium, and high-scoring students when exposed to the team-teaching method. Based on the findings, the study concluded that team teaching did not enhance students’ learning; also, male and female students did not differ in achievement when the team-teaching learning strategy was used. One recommendation for the study is that teachers should use combined teaching methods as an effective strategy in teaching senior school students’ adaptation to biology.